Tác động của mức độ quan tâm của nhà đầu tư tới thị trường chứng khoán Việt Nam - Lê Hải, Trung; Phan Thị Hằng , Ngân; Ngô Thị Thanh , Trúc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study aims to evaluate the impacts of investor attention on the liquidity and volatility of stock returns in the Vietnamese securities market. In particular, the investor attention is proxied by the Google Searching Volume for each individual stock ticker and the stock market from the Google Trends analytics. Our empirical analysis for the top 10 stocks with the largest market capitalization from 1/2018 to 2/2023 reveals that investor attention on individual stock is positively correlated with stock liquidity, while negatively related to its volatility. Interestingly, the authors find that the investor attention on the whole stock market reduces individual stock’s liquidity, while significantly increasing their volatility. This finding can be attributable to the characteristics of the Vietnamese securities market with the majority of retail investors.
Keywords: Stock Market; Investor Attention; Liquidity; Stock Volatility